Los límites de la fragmentación del relato en Cruz de Olvido de Carlos Cortés. - Montero Rodríguez, Shirley (2012)
The present work means to establish the theoretical offer of the paratexts as an important tool in the critical approximation to fiction text. For this, the principal paratexts of the novel Cruz de Olvido of the Costa Rican writer Carlos Cortés are analyzed, this with the intention of establishing the initial proposal of break out, which orientates the entire reading of the literary text.